2016
DOI: 10.1002/jso.24476
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant intraperitoneal chemotherapy for the treatment of gastric cancer at risk for peritoneal carcinomatosis: A systematic review

Abstract: The peritoneal surface is a frequent site of recurrence following surgery for gastric cancer. A systematic review and random effect analysis was undertaken to analyze current literature regarding the role of adjuvant intraperitoneal chemotherapy in gastric cancer. While pooled analysis supports the use of adjuvant IP chemotherapy in resectable gastric cancer, maximal benefit occured with intra-operative delivery, and possibly the use of MMC. J. Surg. Oncol. 2017;115:192-201. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 54 publications
3
34
0
1
Order By: Relevance
“…The efficacy of adjuvant intraperitoneal chemotherapy has been studied for the prevention of peritoneal recurrence after curative resection in patients with locally advanced gastric carcinomas. Cisplatin and mitomycin C have been used as cytotoxic agents for intraperitoneal administration, but their survival benefits have been controversial (42). A meta-analysis showed that the risk of postoperative abscess in the abdominal cavity was increased by 137% in patients with intra-abdominal chemotherapy relative to those receiving surgery alone (43).…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of adjuvant intraperitoneal chemotherapy has been studied for the prevention of peritoneal recurrence after curative resection in patients with locally advanced gastric carcinomas. Cisplatin and mitomycin C have been used as cytotoxic agents for intraperitoneal administration, but their survival benefits have been controversial (42). A meta-analysis showed that the risk of postoperative abscess in the abdominal cavity was increased by 137% in patients with intra-abdominal chemotherapy relative to those receiving surgery alone (43).…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies evaluating CRS and HIPEC were focused on ovarian, appendiceal, and colon cancer. More recent studies have begun to evaluate HIPEC for gastric cancer, but the results have been less promising . Attempts have even been made to expand the indications for this therapy including soft tissue sarcoma and adrenocortical carcinoma, but data is very limited .…”
Section: Regional Therapy For Peritoneal Metastasesmentioning
confidence: 99%
“…More recent studies have begun to evaluate HIPEC for gastric cancer, but the results have been less promising. 61 Attempts have even been made to expand the indications for this therapy including soft tissue sarcoma and adrenocortical carcinoma, but data is very limited. 62 Use of regional peritoneal therapy for pancreas cancer may become an area of greater interest with the advent of more effective systemic treatments.…”
Section: Regional Therapy For Peritoneal Metastasesmentioning
confidence: 99%
“…This trend follows the established management of peritoneal involvement of appendiceal cancer, ovarian cancer and other primary peritoneal surface malignancies [15][16][17][18][19]. There is also a growing body of evidence supporting (IP) chemotherapy as a preventative strategy in gastrointestinal (GI) malignancies, including gastric cancer [20,21]. Preclinically, this strategy is supported by finding that cells undergo epithelial-mesenchymal transition during the peritoneal metastatic process.…”
Section: Introductionmentioning
confidence: 95%
“…Clinically, this strategy has been demonstrated to yield improved survival with the addition of IP chemotherapy in optimally debulked stage-III ovarian cancers [29]. Additionally, there is evidence from multiple randomised phase-II studies in gastric cancer supporting IP chemotherapy at the time of surgery to prevent peritoneal dissemination [20]. Currently, it is not known whether adjuvant IP chemotherapy at the time of definitive surgery might play a useful role in colorectal cancer [10,20,21,30,31].…”
Section: Introductionmentioning
confidence: 99%